2021
DOI: 10.1039/d0cp06606k
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of neodymium and dysprosium from organic electrolytes

Abstract: Nd3+ or Dy3+ salts and borohydride form redox-active [Ln(BH4)4]− complexes that enable room-temperature electrodeposition of neodymium- or dysprosium-containing layers from organic electrolytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 49 publications
3
39
0
Order By: Relevance
“…A 2-fold increase in the average current densities to 1 mA/cm 2 could be achieved upon an increase of the Nd loading to 70 mM and application of a potential of −2.5 V. Irrespective of the differences in the employed electrolyte conditions (i.e., Nd 3+ concentration, viscosity, etc. ), comparable current densities of 0.6 mA/cm 2 were reported in the Li-based electrolyte in THF and dimethyl ether solvents . Noticeably, collected current densities in Nd-loaded electrolytes displayed a significant initial decay before leveling off at lower limiting values under longer deposition times.…”
Section: Resultssupporting
confidence: 65%
“…A 2-fold increase in the average current densities to 1 mA/cm 2 could be achieved upon an increase of the Nd loading to 70 mM and application of a potential of −2.5 V. Irrespective of the differences in the employed electrolyte conditions (i.e., Nd 3+ concentration, viscosity, etc. ), comparable current densities of 0.6 mA/cm 2 were reported in the Li-based electrolyte in THF and dimethyl ether solvents . Noticeably, collected current densities in Nd-loaded electrolytes displayed a significant initial decay before leveling off at lower limiting values under longer deposition times.…”
Section: Resultssupporting
confidence: 65%
“…In addition, DMI, which is an excellent organic solvent with a high boiling point, is also used for large-scale industrial synthesis processes. Therefore, it is superior to conventional ILs for the electrodeposition of RE metals. Figure a shows the deposit formed on an Al foil substrate during potentiostatic electrolysis at −2.5 V (versus Ag/Ag + ) for 4 h at 323 K. A black substance was formed, even in the protective Ar atmosphere. An SEM image of the corresponding cross section is shown in Figure b.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that the electrodeposition of RE metals can be performed successfully using RE-containing perfluorinated salts obtained from phosphonium-, ammonium-, pyrrolidinium-, and imidazolium-based ILs with a sufficiently large electrochemical window. However, the electrolyte systems reported to date for use in the electrodeposition of Nd are based on highly specialized second-generation ILs and are poorly suited for practical electrometallurgical applications owing to the complexity and high cost of their synthesis routes. , In view of this, Periyapperuma et al reported a cleaner approach to recover Nd via electrochemical deposition using low cost and non-fluorinated IL, which is an important step toward Nd recovery . Therefore, inexpensive electrolyte systems and readily available RE precursors are necessary for the facile recovery of RE metals at the lowest possible temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several strategies have been proposed to overcome the limitations of ionic liquids, with the increase of operating temperature, use of organic solvents and neutral ligand-based ionic liquids having been explored. , Of interest to this work, water has been reported as a good promoter for the production of electrochemical REMs in ionic liquids. , Early work on the impact of water was reported by Matsumiya et al, where a slight increase of water content (100–200 ppm) in phosphonium ionic liquids switched the reduction process from a consecutive (1 + 2e – ) reduction into a one-step (3e – ) pathway . In addition to this switch, the peak current decreased and the reduction potential shifted to more negative values.…”
Section: Introductionmentioning
confidence: 99%